Indulgensi di Tahun Yubileum: Dalam Terang Kan. 992-997 KHK 1983 - Joko, Antonius Padua Dwi (Lux et Sal, 2024)
Indulgences and the Jubilee Year hold a close connection within the traditions of the Catholic Church. The Jubilee Year is a special period in the Church's calendar, typically celebrated every 25 years, although the Pope may declare an extraordinary Jubilee for significant occasions. During the Jubilee Year, Catholics are invited to engage in repentance, spiritual renewal, and receive special indulgences. An indulgence itself is the remission of temporal punishment due to sins that have already been forgiven. By obtaining an indulgence, an individual may be freed from part or all of the punishment still owed in this world or in purgatory. Historically, the Jubilee Year has been a sacred time for receiving God's abundant grace, with the indulgences granted during this period serving to strengthen the faithful in their spiritual journey, emphasizing repentance and affirming their faith in God's mercy. In the upcoming Jubilee Year of 2025, as outlined in the Bull Spes Non Confundit, indulgences will once again play a significant role, encouraging the faithful to partake in the grace offered by the Church in an atmosphere of renewed faith.